PENGARUH PEMBELAJARAN KOMPUTERISASI DAN FASILITAS TERHADAP KEMAMPUAN PENGUASAAN APLIKASI MAHASISWA DI FAKULTAS EKONOMI UNIVERSITAS ISLAM SUMATERA UTARA - Nur Augus Fahmi (Universitas Islam Islam Sumatera Utara, 2019)
This research aims to know and explain how the influence of computerized learning and facilities to the mastery ability of application of students at the Faculty of Economics of Islamic University of North Sumatera. In this study use a descriptive method. The data collection techniques used in this study were polls, library studies and interviews to support this research. The purpose of this study is to determine the influence of computerized learning and facilities to the mastery ability of student applications at the Faculty of Economics of Islamic University of North Sumatera. The population in this study is a student management study program that is still active in the faculty of Economics at the Islamic University of North Sumatera, which amounted to 580 people, the sample in this study is 10% of the population, namely of 58 people with a total of 30 questions. Based on analysis and evaluation, the result of calculation using multiple linear regression in the form of T test (partial) between computerized learning (X1) test T (simultaneous) obtained T count t table, which is 6,539 1,672 of Student Application Mastery ability (Y) while relationship or partial correlation between facility (X2) on Student Application Mastery Ability (Y) has t count T table which is 3,768 1,672 and test F (simultaneous) Obtained the value f count = 34,252 F table 2,764 because F count f table, then H0 rejected and Ha accepted then it can be concluded that Silmultan variables free learning ability and the work facility to variable binding ability Application.